Immunomodulatory properties of cell wall extract from Enterococcus faecalis CECT7121 - Sparo, Mónica Delfina (2014)
The aim of this study was to investigate the immunomodulatory properties of cell wall extract from Enterococcus faecalis CECT7121, measuring the induction of cytokines TNF-α, IL-6, IL-10 and IL-12 from human peripheral blood mononuclear cells (PBMCs). Cell wall extract was prepared from their growth in brain heart infusion broth (18. h, 35. °C). Subsequently, toxicity of the obtained cell wall extract was tested in Balb-C mice. PBMCs were isolated from buffy coats at the Blood Transfusion Service of Hospital Ramón Santamarina (Tandil, Argentina). PBMCs were purified using standard Ficoll-Paque gradient centrifugation. Aliquots of purified leukocytes were incubated at 37. °C for 24. h with heat-killed E. faecalis CECT7121 and cell wall extract. Concentrations of IL-6, TNFα, IL-10 and IL-12 (p70) were measured by solid phase sandwich ELISA. Changes in appearance and behavior of mice were evidenced only in the group with the maximal concentration of wall cell extract used (10,000. μg). Cell wall extract and heat-killed E. faecalis CECT7121 induced the production of significantly higher amounts of Il-12, IL-6, TNF-α and IL-10 cytokines compared to the nonstimulated PBMCs. These findings provide helpful information on immunomodulation activity by cell wall extract in sight of the application of this compound in controlling certain infectious diseases.